Analisa Kinerja Pelayanan Angkutan Bus Damri Kota Sorong Berdasarkan Persepsi Pengguna (Studi Kasus : Trayek Sorong – Aitinyo) - Yunita Aprilia; Elfiyusriningsi Syara; Andi Rahmat (CV. Shofanah Media Berkah, 2026)
The rapid growth of Sorong City has increased the need for adequate public transportation to support the mobility of its residents, while also generating benefits for the local economy, socio-cultural life, and the surrounding environment. Among the various public transportation modes available, DAMRI buses are the most widely used by Sorong City residents. To obtain the data, this study applied a purposive sampling technique involving 161 respondents who completed a questionnaire consisting of 21 items. The collected data were then analyzed using the Customer Satisfaction Index (CSI) method, covering three variables: service (X1), facilities (X2), and consumer satisfaction (Y). The analysis results show that the overall satisfaction score of DAMRI bus users reached 79.26%, indicating that passengers were generally satisfied with both the service performance and the facilities provided by DAMRI.